Determination of adequate voltage and animal size for the extraction of spermatophores in the freshwater prawn Macrobrachium acanthurus Determinación del voltaje y el tamaño del animal óptimos para la extracción de espermatóforos en el camarón de agua dulce Macrobrachium acanthurus - Viana da Costa, Tiago (2016)
So far Macrobrachium acanthurus reproduction studies are poorly advanced being important if there is the possibility of cultivation. The aim of this study was to identify the most suitable voltage for the extraction of spermatophores and the smaller size at which these prawns produce them, as a prior step to develop in vitro fertilization techniques. Voltages of 4.5 and 6.0 were used, performing sperm count based on survival of sperm smears, colored with eosin-nigrosine. In the study of size, prawns were separated into class intervals and analyzed for production of spermatophore and sperm survival. The best voltage for the extraction of seminal material due to lower mortality was 6.0 volts and from 5 g of body weight, and 18 mm of length prawns could be used for the extraction of spermatophores.